Patient benefit following bimodal CI-provision: self-reported abilities vs. hearing status - Wallhäußer-Franke, Elisabeth; Balkenhol, Tobias; Hetjens, Svetlana; Rotter, Nicole; Servais, Jérôme J. (Frontiers in neurology, 2018)
Objectives: Patient-reported outcomes gain importance for the assessment of auditory abilities in cochlear implant users and for the evaluation of auditory rehabilitation. Aims of the study were to explore the interrelation of self-reported improvements in auditory ability with improvements in speech comprehension and to identify factors other than audiological improvement that affect self-reported auditory ability. Study Design: Explorative prospective analysis using a within-subjects repeated measures design. Setting: Academic tertiary care center. Participants: Twenty-seven adult participants with bilateral sensorineural hearing loss who received a HiRes 90K CI and continued use of a HA at the non-implanted ear (bimodal hearing). Intervention: Cochlear implantation. Main Outcome Measures: Self-reported auditory ability/disability assessed by the comparative version of the Speech, Spatial and Qualities of Hearing Scale (SSQ-B), and monosyllable as well as sentence comprehension in quiet and within speech modulated noise from different directions assessed pre- as well as 3 and 6 months post-implantation. Results: Data of 17 individuals were analyzed. At the endpoint of the study, improvement of self-reported auditory ability was significant. Regarding audiometric measures, significant improvement was seen for CI-aided pure tone thresholds, for monaural CI-assisted and bimodal sentence comprehension in quiet and in speech-modulated noise that was presented from the same source or at the side of the HA-ear. Correlations between self-reported and audiometric improvements remained weak, with the exception of the improvement seen for monaural CI-aided sentence comprehension in quiet and self-perceived improvement of sound quality. Considerable correlations existed between self-reported improvements and current level of depression and anxiety, and with general self-efficaciousness. Regression analyses substantiated a positive influence of self-efficaciousness on self-reported improvement in speech comprehension and between the improvement of monaural CI-aided sentence comprehension in quiet and perceived sound quality as well as a negative influence of anxiety on self-reported improvement of spatial hearing. Self-reported improvements were significantly better in the subgroup with intensive as compared to regular rehabilitation. Conclusions: Self-reported auditory ability/disability represents an important measure for the success of bimodal CI-provision. It is influenced by personal and mental health factors that may improve CI-rehabilitation results if addressed during rehabilitation.